La alta actividad y el rendimiento académico - Pallo Guamangate, Jessica Silvia (2023)
High activity is a behavior that has generated a conflict in the academic performance of children, however, it is also identified for being a type of learning based on body movement (kinesthetic learning) considered as a teaching method focused on the experiences of the body itself. Therefore, the objective of the project was based on establishing methodological strategies for high activity in the academic performance of third grade students of the "Isidro Ayora" School of General Basic Education in the Latacunga canton. The research was conducted through the qualitative approach, which helped to collect data and allowed understanding the reality within the educational context. On the other hand, the inductive method was used, based on observation, which allowed analyzing the problems that occur in the classroom. On the other hand, the type of research was descriptive, since, in this way it was possible to detail the main characteristics of the children who have this behavior. Therefore, the interview technique was used, which facilitated the collection of the necessary information through an interactive process involving aspects of communication, developing a questionnaire addressed to the teachers of the third years, an instrument used to collect information in an organized manner. The results obtained through the interview with teachers showed that there is a lack of methodological strategies and that there is a need to diversify them in order to apply them in class, since most teachers use the same strategies to keep the child's attention. In the same way, through the observation guide it was shown that in the third year there are children with high activity who present low academic performance. Finally, the research contributes to the strengthening of new methodological strategies, which are based on improving the teaching-learning process of students with high activity that favors the creativity and imagination of the students and in turn facilitates the teacher to teach in a comprehensive and efficient manner, generating an atmosphere of trust within the classroom.